A New Rat Model of Epileptic Spasms Based on Methylazoxymethanol-Induced Malformations of Cortical Development - Kim, Eun-Hee; Yum, Mi-Sun; Lee, Minyoung; Kim, Eun-Jin; Shim, Woo-Hyun; Ko, Tae-Sung (Frontiers in Neurology, 2017)
Malformations of cortical development (MCDs) can cause medically intractable epilepsies and cognitive disabilities in children. We developed a new model of MCD-associated epileptic spasms by treating rats prenatally with methylazoxymethanol acetate (MAM) to induce cortical malformations and postnatally with N-methyl-D-aspartate (NMDA) to induce spasms. To produce cortical malformations to infant rats, two dosages of MAM (15mg/kg, intraperitoneally) were injected to pregnant rats at gestational day 15. In prenatally MAM-exposed rats and the controls, spasms were triggered by single (6 mg/kg on postnatal day 12 (P12) or 10 mg/kg on P13 or 15 mg/kg on P15) or multiple doses (P12, P13, and P15) of NMDA. In prenatally MAM-exposed rats with single NMDA-provoked spasms at P15, we obtain the intracranial electroencephalography and examine the pre-treatment response to adrenocorticotropic hormone (ACTH) or vigabatrin. Rat pups prenatally exposed to MAM exhibited a significantly greater number of spasms in response to single and multiple postnatal NMDA doses than vehicle-exposed controls. Vigabatrin treatment prior to a single NMDA dose on P15 significantly suppressed spasms in MAM group rats (p < 0.05), while ACTH did not. The MAM group also showed significantly higher fast oscillation (25–100 Hz) power during NMDA-induced spasms than controls (p = 0.047). This new model of MCD-based epileptic spasms with corresponding features of human spasms will be valuable for future research of the developmental epilepsy.